Implementasi Pendekatan Saintifik pada Pembelajaran Pendidikan Anak Usia Dini (PAUD) - Munastiwi, Erni (AL-ATHFAL : JURNAL PENDIDIKAN ANAK, 2015)
The learning process which is well managed based on the childrenâs needs and characteristics, is able to optimize the potential of plural intelligence possessed by children from their birth. The learning process is a way to stimulate and reach the optimal capability of the potential intelligence of children. Therefore, the election of the approach in the learning process has to be appropriate to the learning material. One of the approaches in the early learning process is scientific process. The stages of the scientific process are observing, questioning, trying/ collecting,associating, and communating.Â  The implementation of scientific approach is sought in the pleasant atmosphere in order to attract childrenâs interest. The scientific approach is able to build creativity, imagination and idea that develop religious values and morality, motor, cognitive, languge, social, emotional and art based on the principals of childrenâs development. Therefore, the implementation of scientific approach in the learning process of early childhood education can sharpen the childrenâs spiritual and intelectual intelligence.Â